2015
DOI: 10.1002/ejlt.201400623
|View full text |Cite
|
Sign up to set email alerts
|

Quality evaluation of cold‐pressed edible oils from Macedonia

Abstract: The chemical composition and quality of eight pure cold‐pressed oils and two blend oils from Macedonia were examined in this work. The highest level of oleic acid was determined in apricot kernel oil and rapeseed oil with abundance of 70.9 and 59.2%, respectively. The highest level of polyunsaturated fatty acids was seen for flaxseed and hemp seed oil with abundance of α‐linolenic acid of 55.1% for flaxseed oil and linoleic acid of 57.4% for hemp seed oil. Apricot kernel oil and roasted sesame seed oil had the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(16 citation statements)
references
References 38 publications
3
11
2
Order By: Relevance
“…Trace amount of the fatty acids were also identified and these data are similar to those reported by Kostadinovic Velickovska et al, 2015. On the other hand, there are insignificant differences in fatty acid profiles between these results and those reported by Nederal et al, (2014). The differences in profile and amount of certain fatty acids depended on the origin of specific pumpkin (Cucurbita pepo L.) seed oil cultivars, climatic conditions, and post-harvest management (Rabrenovic et al, 2014).…”
Section: Fatty Acid Profilessupporting
confidence: 85%
See 2 more Smart Citations
“…Trace amount of the fatty acids were also identified and these data are similar to those reported by Kostadinovic Velickovska et al, 2015. On the other hand, there are insignificant differences in fatty acid profiles between these results and those reported by Nederal et al, (2014). The differences in profile and amount of certain fatty acids depended on the origin of specific pumpkin (Cucurbita pepo L.) seed oil cultivars, climatic conditions, and post-harvest management (Rabrenovic et al, 2014).…”
Section: Fatty Acid Profilessupporting
confidence: 85%
“…Significantly higher contents of total phytosterols were determined and total phytosterol contents for the PSO samples which ranged from 782.1 ±9.7 to 805.2 ±11.3 mg/100 g oil. Total phytosterol content in the studied samples is significantly higher than the data reported in the literature (Rabrenovic et al, 2014;Kostadinovic Velickovska et al, 2015). Thus, the high total phytosterol contents in the PSO samples from different regions of Turkey may also be related to the species of pumpkin, although the techniques used for oil extraction from seeds and the isolation procedure of phytosterols from oil may also considerably influence data.…”
Section: Phytosterols and Squalene Profilesmentioning
confidence: 58%
See 1 more Smart Citation
“…The data regarding the flavonoid content in cold-pressed oils are very limited. Macedonian flaxseed oil has been shown to contain about three times more flavonoids than samples analyzed in this study [43]. Interestingly, for flaxseed oils from New Zealand, much higher flavonoid levels values (up to 256 mg LE/kg) were noted than values obtained in this study [26,44].…”
Section: Antioxidants Minor Components and Antiradical Scavenging Acontrasting
confidence: 62%
“…Statements in our work are very similar to those made by Tuberoso et al (2007); Kostadinović Veličkovska and Mitrev (2013) and Kostadinović Veličkovska et al (2015) who concluded that free radical scavenging was mainly influenced by the tocopherol content and polyunsaturated fatty acids in oil.…”
Section: Antioxidant Activity By Dpph Assaysupporting
confidence: 91%